The Mediator Role of Emotion Regulation Processes on Infertility-Related Stress - Galhardo, Ana (2018)
The objective of this study is to investigate gender differences regarding the mediator role of selfcompassion and self-judgment on the effects of external shame, internal shame, dyadic adjustment, on infertility-related stress. One hundred and sixty-two women and 147 men with a primary infertility diagnosis completed the following set of self-report measures: Others as Shamer, Experience of Shame Scale, Dyadic Adjustment Scale, Self-Compassion Scale, and Fertility Problem Inventory. Path analyses results revealed that in women self-compassion fully mediated the effect of internal shame on infertility-related stress and partially mediated the effect of dyadic adjustment on this variable, while external shame had only a direct effect. In men self-judgment fully mediated the effect of external and internal shame on infertility-related stress. Dyadic adjustment had only a direct effect on infertility-related stress. In conclusion, there is a distinct role of self-compassion and self-judgment on the relationship between shame and infertility-related stress in men and women. Such differences should be taken into account in psychological interventions with these patients. Future research is warranted to further support our results.